Application of Deep Learning Approach in Physical Education (PE) Students of Senior High Schools - Aditia Putra Munggaran; Tite Juliantine; Sucipto (Journal of Physical Education Health and Sport, 2026)
This research is based on PE learning which tends to be instructive and focuses on technical skills, so that it lacks the development of students' deep understanding and critical thinking skills. The purpose of the study is to analyze the deep learning approach to PE subjects at Senior High Schools 1 Cisolok. The method used was descriptive quantitative with 34 students selected through purposive sampling. The instrument is in the form of a questionnaire of 46 statements that have been tested for validity and reliability, adapted based on the framework of deep learning theory. Data analysis used descriptive statistics, normality tests, and hypothesis tests assisted by SPSS version 25. The results of the study show that the application of the deep learning approach to PE learning has a significant impact. The entire item had a significance value of 0.000 (p < 0.05) with t-counts of 12.324 to 46.278. The conclusion of the study proves that the application of the deep learning approach has a very significant effect on PE learning, improving high-level cognitive aspects, active involvement, meaningful understanding, and student learning character and independence. A deep learning approach is effectively applied in PE to create a holistic and relevant learning experience.